Exploring the Ethnicity and Social Condition of Muslim Calligraphers: A Short Note on Two Scribes from the Horn of Africa in the Mamlūk Period - Gori, Alessandro (Aethiopica, 2023)
Thus far, very little is known of the social origin and position of scribes and calligraphers in the premodern Islamic world. The difficulty in finding data on the biographies and activities of the professional practitioners of calligraphy in historiographical works is probably one of the main causes of this regrettable situation. Taking as a starting point the results of some previous groundbreaking research, the present article gathers scattered information retrieved from different sources about two calligraphers from the Horn of Africa that lived and worked in the Middle East during the Mamlūk period. In the analysis of these two cases, it is hoped that some light will be shed on the presence of calligraphic masters from the Horn in the Arab world from which may be gained, on a more general level, a better picture of the personalities of calligraphers in the Islamic world.